Evaluation of depression, anxiety, alexithymia, attachment, social support and somatization in functional dyspepsia - SAKALLI KANİ, AYŞE; KANİ, HALUK TARIK; YANARTAŞ, ÖMER; ATUĞ, ÖZLEN (TAYLOR & FRANCIS LTD, 2019)
AIM: The psychiatric and psychosocial aetiology of Functional dyspepsia is not well known. In the present study, our aim is to determine the relative contributions of psychiatric predictors - i.e. depression, anxiety, somatization, alexithymia - in relation with socio-psychological factors, specifically their personal characteristics (i.e. emotional attachment) and perceived social support, in distinguishing FD from organic dyspepsia and healthy samples. MATERIAL AND METHODS: An estimated 30 functional dyspepsia, 29 organic dyspepsia patients who were admitted to our gastroenterology outpatient clinic and 27 healthy controls were enrolled to our study. Beck Depression Inventory, Toronto Alexithymia Scale, Adult Attachment Scale, State-Trait Anxiety Inventory, Multidimensional Scale of Perceived Social Support and somatization sub-scale of Symptom Checklist-90 were provided to all patients and healthy controls. All participants were examined by a gastroenterologist and a psychiatrist. RESULTS: Healthy controls were younger than organic dyspepsia group and women/men rate was lower in organic dyspepsia than other two groups. Depression score was higher in functional dyspepsia group than in healthy controls and functional dyspepsia group's attachment syle was more secure than that of the healthy control group. Somatization rate was seen higher in functional dyspepsia group with psychiatric examination. There was no significant difference seen in anxiety, alexithymia and social support between the three groups. DISCUSSION: Anxious-avoidant attachment profile as well as the higher propensity to have depressive and anxiety symptoms might be critical psychiatric and psychosocial factors underlying FD's aetiology. A multidisciplinary approach is needed in the follow up of functional dyspepsia patients. Psychological evaluation and treatment would increase the life quality of dyspepsia patients.
Keywords: Alexithymia; anxiety; attachment; depression; functional dyspepsia; social support; somatization; MEDICALLY UNEXPLAINED SYMPTOMS; HEALTH-CARE UTILIZATION; QUALITY-OF-LIFE; PSYCHOLOGICAL-FACTORS; PSYCHOSOCIAL FACTORS; ADULT ATTACHMENT; DUODENAL-ULCER; GASTROINTESTINAL DISORDERS; DISCRIMINANT-ANALYSIS; PANIC DISORDER